2004
DOI: 10.1002/chem.200305513
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on 195Pt and 205Tl NMR Chemical Shifts of the Complexes [(NC)5PtTl(CN)n]n (n=0–3), and [(NC)5PtTlPt(CN)5]3− Studied by Relativistic Density Functional Theory

Abstract: The 295Pt and 205Tl NMR chemical shifts of the complexes [(NC)5Pt-Tl(CN)n]n- n=0-3, and of the related system [(NC)5Pt--Tl--Pt(CN)5]3- have been computationally investigated. It is demonstrated that based on relativistically optimized geometries, by applying an explicit first solvation shell, an additional implicit solvation model to represent the bulk solvent effects (COSMO model), and a DFT exchange-correlation potential that was specifically designed for the treatment of response properties, that the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 52 publications
4
50
2
Order By: Relevance
“…A similar trend was found for the Pt-O bonds in Table S3 in the SI, where the Pt- 16 O bonds extend further in space than the corresponding Pt- 18 O bond. Note that the zero-point corrections to the eqilibrium PtCl distances are of the same order of magnitude as for the aquo complexes, 24 ca.…”
Section: /37supporting
confidence: 79%
“…A similar trend was found for the Pt-O bonds in Table S3 in the SI, where the Pt- 16 O bonds extend further in space than the corresponding Pt- 18 O bond. Note that the zero-point corrections to the eqilibrium PtCl distances are of the same order of magnitude as for the aquo complexes, 24 ca.…”
Section: /37supporting
confidence: 79%
“…Detailed information can be found in previous papers. 27,28 Selected calculated bond lengths are listed in Table 1 and some of the optimized structures of the solvated complexes I-III and V are shown in Fig. 3.…”
Section: Gcmentioning
confidence: 99%
“…The second section, below, describes the computational details and the computational models that have been applied in this study. The third section briefly reviews the results previously published 27,28 concerning the complexes I-V. The fourth section is devoted to the presentation of the NMR parameters computed for the complexes VI and VII.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that it provides a reasonable accuracy for NMR properties of heavy nuclei in "relativistic" systems, [23,46,[52][53][54][55][56][57][58][59] but not necessarily for light ligand nuclei. Therefore, NMR chemical shifts have additionally been computed by using the Perdew-Wang (PW91) [60] and the BP86 generalized gradient correction (GGA) density functionals in order to analyze the dependence of the results on the approximations in the density functional.…”
Section: Gcmentioning
confidence: 98%